2022
DOI: 10.1101/2022.05.18.22275252
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The expression of cancer stem cells and its effects on the propensity for recurrence and metastasis in bladder cancer: a systematic review

Abstract: Bladder cancer is one of the most frequent cancers of the urinary tract, associated with high recurrence rates and metastasis. Cancer stem cells (CSCs) are a subpopulation of cancer cells characterized by high self-renewal and differentiation capacities, resulting in increased cancer recurrence, larger tumor size, higher rates of metastasis, higher resistance to treatment, and overall poorer prognosis. This study aimed to evaluate the role of CSCs as a prognostic tool to predict the risks of metastasis and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Prior studies of SOX2 expression in bladder cancer support our findings [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Notably, Chui et al showed SOX2 silencing slows bladder cancer growth in spheroid models and reduces spheroid formation [18].…”
Section: Discussionsupporting
confidence: 84%
“…Prior studies of SOX2 expression in bladder cancer support our findings [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Notably, Chui et al showed SOX2 silencing slows bladder cancer growth in spheroid models and reduces spheroid formation [18].…”
Section: Discussionsupporting
confidence: 84%
“…There are some potential mechanisms by which CDK1 expression might contribute to metastasis. CDK1 , as cyclin‐dependent kinase 1, is a pivotal regulator of the cell cycle, driving progression through the G1, S, and G2/M phases 23,24 . Elevated CDK1 expression can lead to uncontrolled cell proliferation, a hallmark of tumorigenesis and a prerequisite for metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…CDK1, as cyclindependent kinase 1, is a pivotal regulator of the cell cycle, driving progression through the G1, S, and G2/M phases. 23,24 Elevated CDK1 expression can lead to uncontrolled cell proliferation, a hallmark of tumorigenesis and a prerequisite for metasta- Machine learning has been avoided in the medical area due to its poor explanation of causality. However, its algorithms with overwhelmingly excellent performances are being developed constantly.…”
Section: Discussionmentioning
confidence: 99%